Penerapan Standar Akuntansi Pemerintahan Dalam Pertanggungjawaban Keuangan Desa: Studi Kasus pada Desa Sigi Kabupaten Pulang Pisau Provinsi Kalimantan Tengah - Donna Octaria; Rahmiati Rahmiati; Septa Soraida; Tatik Zulaika; Rini Oktavia; M. Ichsan Diarsyad (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to find out how government accounting standards are implemented in village financial management in Sigi Village and how prepared the village government is in managing village finances. The research methodology used is qualitative research, the data sources used are primary dtaa obtained by direct interviews and secondary data obtained from related documents. The location of this research is Sigi Village, Kahayan Tengah District, Pulang Pisau Regency, Central Kalimantan Province. The results of this research can be concluded that the implementation of government accounting standards in this village has not been optimal because in the presentation of village financial reports there are still several reports that are not prepared by the village government. Sigi Village Revenue and Expenditure Budget Implementation Report (APBDes), Changes in Excess Budget Balance Report, Realization Report, Cash Flow Report, and Notes to Financial Reports.